2008
DOI: 10.1111/j.1572-0241.2008.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Liver Disease in Blacks, Mexican Americans, and Whites in the United States: Results From NHANES IV, 1999-2004

Abstract: OBJECTIVES Morbidity and mortality due to liver disease and cirrhosis vary significantly by race/ethnicity in the United States. We examined the prevalence of liver disease risk factors among blacks, Mexican Americans, and whites, including elevated aspartate aminotransferase and alanine aminotransferase activity, infection with viral hepatitis B or hepatitis C, alcohol intake, obesity, diabetes, and metabolic syndrome. METHODS Data were obtained from the Fourth National Health and Nutrition Examination Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 30 publications
10
115
1
Order By: Relevance
“…However, only ∼ 10-20% of heavy drinkers develop AC, suggesting a role of other host factors and comorbidities predisposing to ALI and its progression to AC and HCC ( 2 ). Data on genetic predisposition to alcoholism and alcoholic liver disease (ALD) among monozygotic twins ( 3 ), and on ethnic variations on ALD-related mortality independent of amount of alcohol use, support the role of genetic factors in mediating ALD (4)(5)(6). Single-nucleotide polymorphisms within genes of cytokines, alcohol-metabolizing enzymes, and antioxidant enzymes have been shown to be associated with progression of alcohol-induced liver fi brosis ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, only ∼ 10-20% of heavy drinkers develop AC, suggesting a role of other host factors and comorbidities predisposing to ALI and its progression to AC and HCC ( 2 ). Data on genetic predisposition to alcoholism and alcoholic liver disease (ALD) among monozygotic twins ( 3 ), and on ethnic variations on ALD-related mortality independent of amount of alcohol use, support the role of genetic factors in mediating ALD (4)(5)(6). Single-nucleotide polymorphisms within genes of cytokines, alcohol-metabolizing enzymes, and antioxidant enzymes have been shown to be associated with progression of alcohol-induced liver fi brosis ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Flores YN's study, it was found that if the level of education is lower, viral load of hepatitis infection and the incidence of HCC will be more (Flores et al, 2008). Kyunghee Jung-Choi indicated that mortality from the cancer is higher in population groups with lower education than population groups with higher education (Jung-Choi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…First, most studies included Caucasian patients only; hence, the generalizability of our results to other racial/ ethnic groups may be limited. Race/ethnicity is also a potential confounding factor as indicated by fi ndings from several studies, which reported that individuals of Hispanic, black, or Indian race/ethnicity may be more likely to develop cirrhosis compared with Caucasians ( 37,49 ). Additional studies involving participants of different ethnic backgrounds are necessary to further whether differences in the frequency of cirrhosis among different ethnic groups is or is not associated with the rs738409 variant.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…For the GC and GG genotypes compared with the CC genotype, the OR (95% CI) ranged from 1. 49 All seven studies were included in the meta-analyses. Signifi cant heterogeneity was found in the pooled data for evaluation of the G compared with the C allele pooled Therefore, to gain a more comprehensive understanding of the strength of this association, we reviewed the available published literature and carried out meta-analysis to assess the risk of cirrhosis on the basis of rs738409 allele frequency (C vs. G) and genotype (CC vs. GG vs. GC).…”
Section: Evaluation Of the Relationship Of Rs738409 Alleles And Genotmentioning
confidence: 99%